Emotional Intelligence of Future Administration Graduates from an Intercultural University of Peru (Docentes 2.0 Journal, 2024)
Emotional intelligence is a person's ability to recognize, understand, and manage their feelings and emotions and those of others. The objective of this study was to describe the level of emotional intelligence of the students of the undergraduate study program in International Business Administration of the Universidad Nacional Intercultural de la Selva Central Juan Santos Atahualpa post-COVID-19 pandemic. The research was based on inductive and deductive methods, a positivist paradigm, with a quantitative approach, non-experimental design, descriptive type, and cross-sectional. The universe was made up of 230 students. The instrument used for data collection was an emotional intelligence test to measure the students' emotional quotient. The results confirmed that, in the attention factor, 54.5% (55) of male students have adequate attention, while 48.1% (62) of female students pay little attention. 56.5% (57) of male students must improve their clarity for the clarity factor. Regarding female students, 54.3% (70) have adequate clarity. In the repair factor, 56.5% (57) of male students must improve their repair. As for female students, 51.1% (66) have adequate repairs. In conclusion, female students have better levels of emotional intelligence and adequate understanding of their emotional states.
Keywords: Emotional intelligence; Graduates in Administration; Intercultural University; emotional coefficient